Kemampuan Literasi Teknologi Guru Sekolah Dasar Dalam Penggunaan Media Pembelajaran Pada Saat Pandemi Covid-19 - Sulaeman, Tigin; Julia, J.; Gusrayani, Diah (Jurnal Pena Ilmiah, 2021)
This research is based on the framework of thinking that educators must have technological literacy competencies or abilities during the Covid-19 pandemic in making learning media. The research objectives are (1) to determine the technological literacy of teachers during the covid-19 pandemic; (2) knowing the teacher's ability to use learning media during the covid-19 pandemic; (3) knowing the involvement of technological literacy with teachers on the use of learning media during a pandemic. This study focuses on the literacy skills of teachers for online learning, such as making learning media, operating technology devices and how often they use technology in making learning media. This study uses a qualitative method with a survey design. The researcher's first step is to systematically define the participants through random sampling. Furthermore, the researchers made elementary school teachers in the North Sumedang District the object of research. Collecting data by distributing questionnaires. The next step is to process the results of the questionnaire using the Microsoft Excel application and then describe it. The conclusions of the following research are as follows: teacher technology facilities in supporting the manufacture of learning media show good results 49.51% are privately owned, then teacher motivation in using technology tools shows most 58.19% agree that endogenous and exogenous motivation greatly influences. The ability to operate and create learning media is quite high 57.47% of teachers can make technology-based learning media. And the latest findings show that 52.81% of teachers are quite often involved with technology.